Using Student Teams-Achievement Divisions (STAD) Strategy to Improve the Students' Speaking Skill at Vocational School - Rumiarsih Rumiarsih (Universitas Negeri Malang, 2013)
The present study was conducted in order to describe how Student Teams-Achievement Divisions (STAD) Strategy can improve the students' speaking skill. The researcher used Classroom Action Research (CAR) and applied it in the teaching of speaking of XII TKR 2 of SMK Negeri 1 Madiun. The finding of this research indicated that the STAD Strategy was successful in improving the students' speaking skill. The STAD Strategy employed in this study consisted five steps, namely: (1) forming teams; (2) class presentation; (3) quiz; (4) individual improvement score; and (5) team recognition. The activities in those five steps which were don chronologically improved both in the students' speaking achievements and the students' participation during the teaching and learning of speaking. Key Words: speaking skill, student teams-achievement divisions (STAD) strategy